The Growth and Assessment of GaAs Epitaxial Layers Obtained From Ga-As-Bi Solutions - J. Kozlowski; M. Panek; M. Ratuszek; M. Tlaczala (Active and Passive Electronic Components)
X-Ray investigations of GaAs epitaxial layers obtained from Ga-As-Bi solutions with different amounts of bismuth are presented. An equilibrium cooling and two phase technique for the deposition of the GaAs epitaxial layers on semi-insulating GaAs:Cr(100) substrates has been used.